Retail-Level Heroin Enforcement and Property Crime in 30 Cities in Massachusetts, 1980-1986 - Kleiman, Mark A.R. ([Verlag nicht ermittelbar], 1992)
In undertaking this data collection, the principal investigators sought to determine (1) whether police enforcement against drug crimes, specifically heroin crimes, had any influence on the rates of nondrug crimes, and (2) what effect intensive law enforcement programs against drug dealers had on residents where those programs were operating. To achieve these objectives, data on crime rates for seven successive years were collected from police records of 30 cities in Massachusetts. Data were collected for the following offenses: murder, rape, robbery, assault, larceny, and automobile theft. The investigators also interviewed a sample of residents from 3 of those 30 cities. Residents were queried about their opinions of the most serious problem facing people today, their degree of concern about being victims of crime, and their opinions of the effectiveness of law enforcement agencies in handling drug problems.